Analysis of the Influence of Product Quality, Brand Image, and Price on Purchasing Decisions of Kopi Kenangan Cipayung, East Jakarta - Fatrick Kristopher, Fatrick Kristopher; Sam’un, Mohamad (Peneliti.net, 2024)
This study aims to analyse the effect of product quality, brand image, and price on purchasing decisions for Kopi Kenangan. The sampling method used was non-probability sampling with a sample of 105 respondents. Sampling using purposive sampling method with respondents selected based on criteria who have bought Kopi Kenangan products at the Cipayung Kenangan Coffee shop and are at least 16 years old and above. The data used in this study consisted of primary data and secondary data. The data collection technique was carried out by distributing questionnaires to respondents using a Likert scale followed by the Successive Interval Method (MSI). Instrument tests use validity and reliability tests. The data analysis used is multiple regression analysis with data that has been calculated using classical assumptions consisting of normality test, linearity test, multicollinearity test, and heteroscedasticity test. Data processing was carried out with the SPSS ver. 20 and Microsoft Excel. Based on the research results that product quality, brand image, and price simultaneously influence the purchasing decision of Kopi Kenangan Cipayung. And partially product quality and brand image have an effect on purchasing decisions for Cipayung Memories Coffee while price has no effect on purchasing decisions for Cipayung Memories Coffee. It is recommended that companies can pay attention to product quality and brand image so that purchasing decisions can increase with product improvement and innovation. Keywords: brand image, price, and product quality purchasing decisions.